Internet-based environmental education: An experimental study applying the simulation game SimUlme in school - Hansmann, Ralf; Hesske, Stefan; Tietje, Olaf; Scholz, Roland (Swiss Journal of Educational Research, 2002)
An Internet based simulation game on ecological and economical consequences of nutrition consumption has been developed to improve environmental knowledge and attitudes in a playful and vivid way. In the experiment 12 classes were instructed on the consequences of nutrition consumption, 6 classes with application of the «SimUlme» learning game (experimental condition), 6 classes without it (control condition). The comprehensiveness, active participation, and engagement of the students in the experimental condition were judged significantly more positive than in the control condition. The tendency toward positive changes of environmental attitudes concerning nutrition behavior was more marked in the experimental condition as compared to the control condition. The lessons in the two conditions improved environmental knowledge in a complementary way. The results indicate that adequate Internet games can effectively support education in school.